Stem Cell Plasticity and Dormancy in the Development of Cancer Therapy Resistance - De Angelis, Maria Laura; Francescangeli, Federica; La Torre, Filippo; Zeuner, Ann (Frontiers in Oncology, 2019)
Cancer treatment with either standard chemotherapy or targeted agents often results in the emergence of drug-refractory cell populations, ultimately leading to therapy failure. The biological features of drug resistant cells are largely overlapping with those of cancer stem cells and include heterogeneity, plasticity, self-renewal ability and tumor-initiating capacity. Moreover, drug resistance is usually characterized by a suppression of proliferation that can manifest as quiescence, dormancy, senescence or proliferative slowdown. Alterations in key cellular pathways such as autophagy, unfolded protein response or redox signaling, as well as metabolic adaptations also contribute to the establishment of drug resistance, thus representing attractive therapeutic targets. Moreover, a complex interplay of drug resistant cells with the micro/macroenvironment and with the immune system plays a key role in dictating and maintaining the resistance phenotype. Recent studies have challenged traditional views of cancer drug resistance providing innovative perspectives, establishing new connections between drug resistant cells and their environment and indicating unexpected therapeutic strategies. In this review we discuss recent advancements in understanding the mechanisms underlying drug resistance and we report novel targeting agents able to overcome the drug resistant status, with particular focus on strategies directed against dormant cells. Research on drug resistant cancer cells will take us one step forward towards the development of novel treatment approaches and the improvement of relapse-free survival in solid and hematological cancer patients.